2008
DOI: 10.3748/wjg.14.469
|View full text |Cite
|
Sign up to set email alerts
|

Single-center study comparing computed tomography colonography with conventional colonoscopy

Abstract: diagnosis of cancer, eight (89%) were identified by CT colonography as masses (5) or polyps (3). For polyps analyzed according to polyp, the overall sensitivity of CT colonography was 50% (95% CI, 39%-61%) but this increased to 71% (95% CI, 52%-85%) for polyps ≥ 6 mm in size. Similarly, specificity for all polyps was 48% (95% CI, 39%-58%) increasing to 67% (95% CI, 56%-76%) for polyps ≥ 6 mm. Adverse events were uncommon but included one colonic perforation at colonoscopy. Patient acceptance was high for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We included 47 prospective studies involving 10,546 patients that compared CTC to the reference standard of CC or surgery [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]. Table 2 shows detailed information from individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…We included 47 prospective studies involving 10,546 patients that compared CTC to the reference standard of CC or surgery [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]. Table 2 shows detailed information from individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed patient preferences for CTC and colonoscopy in 130 patients who had recently undergone both tests as part of a diagnostic accuracy study [23]. Participants had indications appropriate for diagnostic colonoscopy, including bowel symptoms, positive faecal occult blood tests, or a family history of colorectal cancer.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a pilot study of the DCE in ten people who had experienced both CT colonography and colonoscopy as part of a pilot for the diagnostic accuracy trial [23]. Results indicated that respondents were able to understand attribute descriptions and levels and complete the 32 discrete choice questions without undue burden.…”
Section: Methodsmentioning
confidence: 99%
“…Another disadvantage of virtual colonoscopy is the false negative or false positive rates. The most common reasons are inadequate colon preparation, inadequate distention and bulbous haustral fold (Hara et al, 2001;Halligan et al, 2006;Ferrucci, 2001;Roberts-Thomson et al, 2008). Screening in prone or supine position or administration of IV contrast agent might be helpful to avoid confusing polyps with residual fecal material.…”
Section: Advantages and Disadvantages Of Virtual Colonoscopymentioning
confidence: 99%
“…(Kim et al, 2007;Macari et al, 2011;Pedersen et al, 2003;Pescatore et al, 2000;Pickhardt et al, 2011;Pilch-Kowalczyk et al, 2004;Roberts-Thomson et al, 2008;Sutherland et al, 2011;White et al, 2009) (Fig 3,4). Virtual examinations carry the advantages including being relatively noninvasive, safe, and acceptable by clinicians (Ekci & Yildirim, 2009;Johnson & Dackman., 2000;Leksowski el al., 2011;McHugh et al, 2011;Vining, 1996).…”
Section: Advantages and Disadvantages Of Virtual Colonoscopymentioning
confidence: 99%